Budaya Politik : Partisipasi Masyarakat Desa Ciwaringin Kecamatan Ciwaringin, kabupaten Cirebon - Hendri Suwarsono (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Political culture plays an important role in determining the dynamics of general elections, especially in the context of Regional Head Elections (Pilkada) in Indonesia. This research focuses on Ciwaringin Village in Ciwaringin District, Cirebon Regency, which shows low community political participation due to a parochial political culture. People in this village tend to be inactive in the election process, are influenced by the practice of money politics, and choose based on personal closeness and material lures, without understanding the vision and mission of potential leaders. This research uses a qualitative approach with literature study and interview methods to explore the factors that influence political participation, including social, economic, and educational aspects and the use of information media. Findings show that low political literacy and indifference to political issues result in apathy toward elections. Therefore, educational efforts and increasing political awareness are needed to encourage active community participation in the democratic process. It is hoped that this research can contribute to understanding political culture and community participation in Ciwaringin village and promote improvements in implementing the upcoming regional elections.